Pembuatan Busana Pesta Fantasi Dengan Teknik Manipulation Textile Stitch And Slash - Romdhona Chusna Tsani; Indah Meilia Ardiani (Akademi Kesejahteraan Sosial Ibu Kartini Semarang, 2023)
Fantasy clothing is clothing that is designed as creatively as possible without leaving the characteristics of the source of the idea. One of the techniques used to make fantasy party dresses is the textile stitch and slash technique. The stitch and slash technique is a textile processing technique by changing the texture of the cloth to get a different impression so as to add aesthetic value. The purpose of applying the stitch and slash technique to fantasy clothing is so that the clothing has aesthetic value and high selling value. The method used is a qualitative method using data collection such as observation, literature and documentation as well as data analysis. The process of making fantasy party dresses with the manipulation textile stitch and slash technique starts from making designs, analyzing designs, preparing tools and materials, sizes, basic patterns, breaking patterns, cutting materials, merging, sewing, and the finished product. Making fantasy party dresses with manipulation textile stitch and slash using satin and chiffon fabrics. Making clothes using the stitch and slash technique needs to pay attention to the layers that are stacked to produce fiber thickness, using a brush that has stiff bristles can help remove the fibers so as to produce a good stitch and slash texture and to make it easier to sew stitch and slash on clothing, pins are needed. so that the layer stack does not shift.